Clarification of the clinical significance of an intron variant in a case of Peutz–Jeghers syndrome with abnormal RNA splicing of STK11 - Aki Ishikawa; Masahiro Gotoh; Mineko Ushiama; Hiromi Sakamoto; Noriko Tanabe; Tomoko Watanabe; Hourin Cho; Masayoshi Yamada; Kokichi Sugano; Kouya Shiraishi; Makoto Hirata; Teruhiko Yoshida; et al. (Molecular Cytogenetics)
Abstract Peutz–Jeghers syndrome is an autosomal dominant disease characterized by intestinal polyposis, mucocutaneous pigmentation, and an increased risk of various types of cancer. Germline mutations in STK11 (LKB1), which encodes serine/threonine kinase 11, have been identified as the major cause of Peutz–Jeghers syndrome. Here, we detected a rare variant of undetermined significance in intron 2 of STK11 using multi-gene panel analysis in a girl with clinically suspected Peutz–Jeghers syndrome. We confirmed this variant caused abnormal splicing in exons 2 and 3 using reverse transcription-PCR and Sanger sequencing. To validate the predicted impact of this variant on splicing, we performed functional analysis using a minigene assay. Functional analysis experiments demonstrated that this variant suppresses normal splicing, and the clinical significance of the STK11 variant, which was initially considered a variant of “uncertain significance,” was reclassified as “likely pathogenic” based on functional analysis. The interpretation of U12-type intronic variants remains particularly challenging due to limited data and the absence of specific recommendations in existing guidelines [1, 2], and when segregation analysis is difficult, functional analysis from splicing assays is essential to provide accurate genetic diagnosis and information for clinical management. However, further familial segregation analysis and further validation of potential exon-skipping events are necessary to fully characterize the splicing impact of this variant.